Clues to seismic data interpretation within the zones of the sand injections in so called "anomalous section" of the Bazhenovo Black Shales formation on the examples of the Potochnaya, Sporyshevskaya, Vyintoiskaya and Vatinskaya zones - Gatina Nadezhda; Sarieva Marina; Mukhutdinova Oksana; Popkov Andrey; Gavrilov Sergey (Russian Journal of Earth Sciences, 2023)
The Bazhenovo horizon of Western Siberia has traditionally been one of the objects most studied by geologists and geophysicists in recent decades in Russia. However, along with the more familiar "classical" structure, there are areas where gray-colored inclusions of sandy-silty-clayey deposits are present between the carbonate-clayey-siliceous rocks of the Bazhenovo Black Shales Formation. Such sections geologists call "anomalous". The paper describes the application of the spectral decomposition method for detailing the structure of anomalous sections zones of the Bazhenovo Formation or in another words Giant Sand injection Complex (GSIC) of the Ob river region. Combining the results of dynamic interpretation of 3D seismic data with well logging data for a vast fund of exploration and production wells made it possible to build a seismogeological model of the of the Ob river region GSIC in the Potochnaya area. The clue approach was tested on the Sporyshevskaya and Vyyntoyskaya, Vatinskaya areas, which were much less explored by drilling. The listed zones were formed at different geological times, belong to different regional clinoforms, but have common patterns of structure, which is reflected in the seismogeological model of the Ob river region GSIC. The model describes the distal and proximal parts of the intrusion, which were formed in the Neocomian time, when gravity-driven flows of sandy-silty material injected and spread inside high-bituminous Jurasic Bazhenovo formation Black Shales. Within the proximal part gravity-driven flows were accompanied by slumps of more clayey rocks. The dimensions of these flows and slumps, their location over the area are shown, their mapping in the 3D seismic data is discussed. In this work, we managed to get closer to solving the problem of predicting the development of sandy downward intrusions. There are oil reservoirs in the Ob river region GSIC, but they are insufficiently studied.